RELATIONSHIP OF KNOWLEDGE AND WORK MOTIVATION OF NURSES WITH ATTITUDES TO SUPPORT THE APPLICATION OF PATIENT SAFETY INPATIENT ROOM OF WONOSARI YOGYAKARTA GENERAL HOSPITAL - Fransiska Tatto Dua Lembang (Universitas Respati Yogyakarta, 2021)
The application of patient safety goals is a mandatory system that must be implemented by nurses in hospitals so that patient safety is guaranteed. Increasing the level of knowledge and work motivation of nurses is expected to support the expectations of patient safety goals and efforts to minimize unexpected events. The high incidence of patient safety in the hospital illustrates that nurses still lack understanding of the importance of patient safety. Knowing the relationship between the level of knowledge and work motivation of nurses with the attitude of supporting the implementation of patient safety goals in the inpatient room of RSUD Wonosari YogyakartaThis research is a quantitative analytic descriptive correlation study with a cross sectional approach. The population sample in this study were 60 nurses at Wonosari Yogyakarta Hospital. The sampling technique used stratified random sampling, and data analysis used the Spearman Rank. The results of the spearman rank correlation test stated that there was no relationship between the level of knowledge and attitudes to support the implementation of patient safety targets by nurses in the inpatient room of RSUD Wonosari Yogyakarta with a p value of 0.323> 0.05. There is a relationship between the work motivation of nurses and the attitude of supporting the implementation of patient safety goals in the inpatient room of RSUD Wonosari Yogyakarta with a p value of 0.049 <0.05. There is no relationship between the level of knowledge and attitudes to support the implementation of patient safety goals by nurses in the inpatient room of RSUD Wonosari Yogyakarta. There is a relationship between the work motivation of nurses and the attitude of supporting the implementation of patient safety goals in the inpatient room of Wonosari Yogyakarta Hospital Keywords: Patient Safety; Knowledge; Motivation; Nurses